Characterization of a Diguanylate Cyclase VAGM001033 of Vibrio alginolyticus and Protective Efficacy as a Live Attenuated Vaccine Candidate in Pearl Gentian Grouper - Tan, Huiming; Da, Fan; Lin, Guixiang; Wan, Xiaoju; Jian, Jichang; Cai, Shuanghu (Frontiers in Marine Science, 2022)
Vibrio alginolyticus (V. alginolyticus) is one of the important epizootic pathogens in marine animals. VAGM001033 belongs to a diguanylate cyclase, responsible for the synthesis of dimeric guanosine monophosphate (c-di-GMP), a ubiquitous second messenger involved in the function of biofilm formation, motility, and virulence. This study confirmed that VAGM001033 was an active diguanylate cyclase by Congo red assay. The red-stained, dry, and rough form of colonies were observed with the increasing concentration of the L-arabinose on Congo red plates. Also, an in-frame deleted ΔVAGM001033 mutant was constructed and changes of ΔVAGM001033 mutant in physiology and pathogenicity were detected. The ΔVAGM001033 mutant displayed similar morphology and growth curve with the wild-type strain showing no significant differences. The swarming ability of the ΔVAGM001033 mutant was significantly enhanced showing bigger swarming circles, while the biofilm formation, extracellular proteases, and virulence were significantly attenuated. The results of the test for antibiotic susceptibility showed that the wild type and ΔVAGM001033 mutant had similar sensitivity or resistance to most antibiotics used in this study, except cefotaxime and nitrofurantoin. The mutant was sensitive to cefotaxime and nitrofurantoin, while the wild type was intermediate. A total of 756 differentially expressed genes (DEGs) were identified by RNA-seq, of which 109 were upregulated and 647 were downregulated. Flagellar assembly, two-component system, ATP-binding cassette (ABC) transporters, and peptidoglycan biosynthesis were significantly enriched in the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway. Moreover, the ΔVAGM001033 mutant induced high antibody titers and provided immune protectivity with a relative percent survival (RPS) of 82%. Immune-related genes of pearl gentian grouper (♀Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus), namely, IgM, MHC-Iα, interleukin-1β (IL-1β), interleukin-16 (IL-16), and tumor necrosis factor-α (TNF-α) were upregulated after vaccination. Overall, the results suggested that VAGM001033 plays a crucial role in V. alginolyticus. The ΔVAGM001033 mutant might be applied as an effective live vaccine candidate against V. alginolyticus.